Help-seeking duration and its impact on the course of non-suicidal self-injury and suicide attempts in outpatient adolescents - Driesch, Luisa von den; Cavelti, Marialuisa; Josi, Johannes; Koenig, Julian; Reichl, Corinna; Kaess, Michael (Journal of psychiatric research, 2025)
Background - Adolescents with self-harming behavior (comprising non-suicidal self-injury [NSSI] and suicidal behavior) do often not seek professional help or do so with delay. The aim of this study was to investigate (i) the relationship between the duration of help-seeking (HS-DU) for first NSSI and frequency of NSSI at 1-year follow-up, and (ii) the relationship between HS-DU for first NSSI, suicidal thoughts, suicide attempts and frequency of suicide attempts at follow-up in a cohort of adolescents seeking treatment for self-harm. - Methods - This sample consisted of 285 adolescent outpatients (88 % female, mean age = 15.11 ± 1.44 years). Time from symptom onset to first contact with professional care was assessed as a predictor variable at baseline. Frequency of suicide attempts in the previous year and frequency of NSSI in the past 6 months were assessed as outcome variables at baseline and 1-year follow-up. Generalized linear mixed models were used to assess associations between HS-DU for each variable and NSSI or suicide attempts at follow-up, controlling for age and gender. - Results - There was a significant decrease in the frequency of self-harm between baseline and 1-year follow-up. However, help-seeking duration for NSSI, suicidal thoughts or suicide attempt was not significantly associated with NSSI or suicide attempts at follow-up. - Discussion - Duration between onset of suicidal thoughts and self-harm and first contact with mental health services was not associated with the treatment outcome of self-harm. Clinically, this may indicate that self-harm can still be effectively reduced by intervention, even if professional help is sought late.
Gesehen am 09.09.2025